2019
DOI: 10.1038/s41598-019-46671-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of gold nanoparticles on DSS-induced ulcerative colitis in mice with reference to interleukin-17 expression

Abstract: Ulcerative colitis (UC) is among the most challenging human diseases. Nanotechnology has incontestable promising outcomes in inflammatory bowel diseases. This study aimed to investigate the therapeutic effect of naked gold nanoparticles (AuNPs) on dextran sodium sulphate (DSS) induced ulcerative colitis in mice. We also examined the expression of interleukin-17 (IL-17) following AuNPs treatment. Mice were randomly divided into control, DSS and DSS+ AuNPs groups. Severity of colitis was assessed by disease acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 72 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…These findings indicated that IL-17 is associated with the development and progression of UC, and suggested that IL-17 is an attractive therapeutic target. For many years, researchers have been exploring the new IL-17-based treatment schemes [33][34][35] , although the results of clinical trials with anti-IL-17 antibodies in inflammatory bowel disease (IBD) were discouraging 36 . Our previous study demonstrated that orally administered MA could obviously attenuate colitis by downregulating the expression of IL-17 in colon tissue of colitis mice 16 , but the IL-17-producing effector cells remain undefined.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that IL-17 is associated with the development and progression of UC, and suggested that IL-17 is an attractive therapeutic target. For many years, researchers have been exploring the new IL-17-based treatment schemes [33][34][35] , although the results of clinical trials with anti-IL-17 antibodies in inflammatory bowel disease (IBD) were discouraging 36 . Our previous study demonstrated that orally administered MA could obviously attenuate colitis by downregulating the expression of IL-17 in colon tissue of colitis mice 16 , but the IL-17-producing effector cells remain undefined.…”
Section: Discussionmentioning
confidence: 99%
“…6 PEA is an anti-inammatory compound that activates peroxisome proliferator-activated receptor-a-dependent (PPARa) and exhibit benecial effects on inammations. 1,20 F96 is a NAAA inhibitor that selectively and potently inhibit NAAA, lead to anti-inammatory effects in many different inammation experimental models. 7 We used undifferentiated Caco-2 cells to examine the toxicity where F96 did not show signicant toxicity.…”
Section: Discussionmentioning
confidence: 99%
“… 18 For example, Au nanoparticles coated with tiopronin and smaller than 10 nm were introduced to verify the treatment efficiency. 55 Compared with nanoparticles larger than 10 nm, the system with the smaller nanoparticles can be absorbed by intestinal epithelial cells faster and diffuse through the interior of the cells. This drug-loading system has been shown proven to inhibit the production of ROS, scavenge free radicals, and improve the antioxidant enzyme activity in diabetic mice.…”
Section: Passively and Actively Targeted Drug Deliverymentioning
confidence: 99%
“…Due to the increased permeability of the vessels and epithelium in of IBD, nanocarriers with sizes from 10 to 200 nm can accumulate and penetrate through the intestinal mucosa through the eEPR effect, thereby increasing the residence time in the target area and improving the efficacy of the drug. [53][54][55] This effect is based on the histopathological abnormalities of colon tissue, such as the loss of barrier functions caused by the rupture of the intestinal epithelial cells, the increase in epithelial permeability, and the obvious infiltration of inflammatory cells into the mucosa. 56 Notably, as we all know, the toxicity and side effects of metal nanoparticles such as those consisting of Au and Ag elements with small particle sizes cannot be ignored.…”
Section: Passive Targetingmentioning
confidence: 99%